THE PUBLIC LENDING RIGHT (PLR) - Ana-Maria MARINESCU (Challenges of the Knowledge Society)
The study underlines the main characteristics of the public lending right (PLR) and the systems implemented at the level of the European Union and also internationally. In brief, the public lending right (PLR) is the economic right that allows authors and other copyright owners to receive payments in order to compensate the free loan of their books by public and other libraries. Usually, the payments are ensured by the state budget of the state in which the system is implemented. Most PLR systems are founded in Europe (Denmark being the first country to establish a PLR system in 1946, followed by Norway in 1947 and Sweden in 1954), where the member states of the European Union are required by law, under the Rental and Lending Right Directive (Directive 2006/115/EC), to provide authors with an exclusive right over the lending out of their works or at least to provide them with a remuneration for the lending out of their works. Other systems are implemented also internationally, at the present in the world are established 33 systems and 27 countries are counted as in development, even that the public lending right is not compulsory required under any international convention or treaty, by consequence the states are not obliged to regulate or to implement it. This demonstrates the importance of the public lending right in the general context of copyright development and infrastructure. Also, the study draws attention to the fact that in Romania the system is neither implemented nor functional, which has caused prejudice to authors and other copyright holders who have not been remunerated for the use of their works through the public lending made in libraries.